MODEL 3D IMPLAN LUTUT FEMUR DARI REKONSTRUKSI TULANG LUTUT DENGAN METODE REVERSE ENGINEERING BERBANTUAN PEMINDAI CT-SCAN - Harun, Suryadiwansa; Ismunandar, Helmi; Burhanuddin, Yanuar; Supriyadi, Satrio Darma (Jurnal Rekayasa Mesin, 2024)
As a person ages, usually after age 50, knee joint bone damage caused by osteoarthritis can occur. It is to cause pain in the knee joint so that its function moves abnormally. The knee joint bone damage could be replaced with a prosthesis (Total Knee Replacement, TKR) to restore the knee joint's normal movement function. However, orthopaedic doctors sometimes have difficulty choosing standard implant designs available for patients' knees when performing TKR surgery, especially for Asian patients, including Indonesians. It is due to the geometry of the standard implant being different from the patient's knee anatomical shape. As a result, postoperative pain reactions can occur. Therefore, this study is to customize the TKR femoral implant's design according to the knee bone's geometry, especially in Indonesian patients. Reverse Engineering (RE) technology assisted by the CT-Scan and the boundary surface technique was applied for reconstructing the patient's knee bone into a femoral implant. The application of RE is initially, the patient's knee bone sample was scanned with Computer Tomography (CT) Scan. Then, the femur implant model was designed on the surface of the patient's knee bone using the boundary surface method. The 3D model of the TKR femoral implant was successfully designed to match the geometry of the patient's femur bone. It will be a reference for designing other TKR implants, namely the tibia component.